Legume fertilizers as alternative sources of nitrogen for organic lettuce production - Almeida, Maxwell Merçon Tezolin Barros; Lixa, Alice Teodorio; Silva, Edmilson Evangelista da; Azevedo, Pedro Henrique Sabadin de; De-Polli, Helvécio; Ribeiro, Raul de Lucena Duarte (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to evaluate the potential use of two legume fertilizers – products derived from cutting, dehydration and milling of the aerial biomass of legume plants, velvet bean (Mucuna pruriens) and gliricidia (Gliricidia sepium) – as alternative sources of N for organic production of lettuce (Lactuca sativa cv. Vera); and to evaluate the influence of soil fertilization on lettuce shelf life at laboratory bench condition. These fertilizers were applied on soil surface and compared to factory poultry-bed manure at equivalent total N doses. The experimental design consisted of randomized blocks with five treatments and four replications, as following: T1: pre-planting fertilization with magnesium thermophosphate + potassium sulphate; T2: T1 + cattle manure in pre-planting; T3: T2 + velvet bean fertilizer in covering; T4: T2 + gliricidia fertilizer in covering; and T5: T2 + poultry-bed manure in covering. Fertilizers of both legume species were not statistically different of poultry-bed manure, regarding productivity, N content, commercial standard and shelf life of lettuce, which indicates promising potential for their use in organic horticultural production systems.
Keywords: Gliricidia sepium; Lactuca sativa; Mucuna pruriens; green manuring; poultry-bed manure; postharvest